PERANCANGAN BUKU KATALOG MUSEUM KESEHATAN SURABAYA MENGGUNAKAN TEKNIK FOTOGRAFI SEBAGAI UPAYA PENGENALAN WISATA EDUKASI TERHADAP PELAJAR DI KOTA SURABAYA - Anggriawan, Dede Triastanto; Martono, Siswo; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Surabaya city filled with various kinds of uniqueness and history that preceded. But we need to know there are still many historical relics that exist in surabaya especially the museum of heroes monument is where the first president of Indonesia Ir.Soekarno declare the text of the proclamation as well as in there are historical events such as reading the text of the proclamation of Bung Tomo who in the era of penjajahn Giving spirit, courage and willingness to die to seize the seized power of the allies. As well as the story of surabaya people who fought against the invaders. Objects - objects such as weapons, clothing, art, and others.But not all people surabaya recognize the Surabaya health museum and especially for students who often do research but do not know the existence of Surabaya health museum, this is based on the results of interviews conducted on the head of the health museum Surabaya. Minimnya less knowledge of society, especially for students in the city surabaya.The purpose of this study is to design a book catalog of health museum Surabaya using photography techniques with this can inform the students in the city of Surabaya.Researcher conducted by using qualitative research method, with technique of collecting data through interview, observation, documentation, existing study and literature study. The results of data analysis, then in the reduction to find keywords that lead to communication strategy book that will be used. By raising "Different" as a keyword that has been found, the word "Different" is defined differently from the others, that is, the book catalog of museums that distinguishes more specifications describes the collection and the results of photography is clear.The result of designing the catalog book of Surabaya Health Museum as well as its media empowerment has made informative and educative elements about Surabaya health museum collections, so it is expected to be a medium to find out information about the health museum collections of Surabaya.Kata Kunci: Perancangan, Buku Katalog, pendidikan sejarah, Fotografi